AlGaN-based ultraviolet LED chip with dual polarization inducing doping layer and preparation method thereof

By using component gradient AlGaN in AlGaN-based UV LEDs to achieve polarization-induced doping, the problem of low luminescence efficiency of AlGaN-based UV LEDs is solved, the luminescence performance of short-wavelength LEDs is improved and the production process is simplified.

CN114823998BActive Publication Date: 2025-02-18JILIN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210544131.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-18
Publication Date
2025-02-18
Estimated Expiration
2042-05-18

AI Technical Summary

Technical Problem

The luminescence efficiency of AlGaN-based ultraviolet LEDs is low, especially short-wavelength LEDs. In their structure, the p-type doping and n-type doping of the high Al component AlGaN are difficult, resulting in difficulty in improving the luminescence efficiency.

Method used

The component gradient AlGaN is used to achieve the polarization of the high carrier concentration of AlGaN materials, and the n-type doping layer and the component gradient AlyGa1-yN polarization are induced by the component gradient AlxGa1-xN polarization. Induce the p-type doping layer to improve the luminous performance of LEDs.

Benefits of technology

The luminescence performance of AlGaN-based UV LEDs, especially short-wavelength LEDs, achieve efficient luminescence, simplify device manufacturing processes, and reduce lattice mismatch dislocation density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114823998B_ABST
    Figure CN114823998B_ABST
Patent Text Reader

Abstract

An AlGaN-based ultraviolet LED chip with a dual polarization induced doping layer and a preparation method thereof belong to the technical field of semiconductor light-emitting devices. The chip comprises a substrate, an AlN template layer, and a composition gradient Al x Ga 1‑ x N-polarization induced n-type doped layer, active area light-emitting layer, composition gradient Al y Ga 1‑y The present invention uses AlGaN with a gradient component to achieve high carrier concentration polarization induced n-type and p-type doping of AlGaN materials, which is beneficial to improving the luminescence performance of AlGaN-based ultraviolet LEDs. y Ga 1‑y The N-polarization induced p-type doped layer can eliminate the absorption of ultraviolet light in the active area by the p-GaN layer in the traditional ultraviolet LED structure, and realize the efficient light emission of AlGaN-based ultraviolet LEDs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor light-emitting devices, and in particular relates to an AlGaN-based ultraviolet LED chip with a dual-polarization inducing doping layer and a preparation method thereof. Background Art

[0002] With the continuous development of III-nitride semiconductor LED technology, its market application prospects are also expanding, especially AlGaN-based ultraviolet LEDs, which have great application potential in the fields of air purification, disinfection and sterilization. As a direct bandgap semiconductor material, AlGaN can continuously adjust its bandgap width between 3.4 and 6.2eV by regulating the Al component, and the emission wavelength covers a range of 365 to 200nm. It is an ideal material for preparing ultraviolet LEDs. Compared with traditional ultraviolet light sources such as ultraviolet mercury lamps and xenon lamps, AlGaN-based ultraviolet LEDs have the advantages of high efficiency and energy saving, safety and environmental protection, reliability and durability, and small size. However, the current luminous efficiency of AlGaN-based ultraviolet LEDs is relatively low, mostly below 10%, and its luminous efficiency decreases exponentially as the wavelength becomes shorter. AlGaN materials are usually p-type through Mg acceptor doping, and the activation energy of Mg acceptors in AlGaN materials is large and increases linearly with the increase of Al components (from 150meV of GaN materials to 600meV of AlN materials). The high activation energy of Mg acceptors makes it difficult to dope AlGaN materials with p-type, that is, its hole concentration is low, which is one of the important reasons for the low luminous efficiency of AlGaN-based ultraviolet LEDs. At the same time, with the increase of the Al component of AlGaN materials, the activation energy of Si donors in the material will gradually increase (from about 20meV for GaN to about 250meV for AlN). Therefore, for short-wavelength AlGaN-based ultraviolet LEDs, it will be very difficult to dope p-type and n-type AlGaN with high Al component in its structure, which also makes it more difficult to improve the luminous efficiency of short-wavelength AlGaN-based ultraviolet LEDs. Summary of the invention

[0003] The purpose of the present invention is to solve the problem of low luminous efficiency of the above-mentioned AlGaN-based ultraviolet LED, and comprehensively consider aspects such as improving the p-type and n-type carrier concentrations of the AlGaN material and the crystal quality of the epitaxial layer, simplifying the device manufacturing process and improving the device performance, and propose an AlGaN-based ultraviolet LED chip structure with a dual polarization induced doping layer and a preparation method thereof. In the ultraviolet LED device structure, the high carrier concentration polarization induced n-type and p-type doping of the AlGaN material is achieved by using the component gradient AlGaN, which is beneficial to improving the luminous performance of the AlGaN-based ultraviolet LED, especially the short-wavelength AlGaN-based ultraviolet LED.

[0004] The technical solution of the present invention is:

[0005] The AlGaN-based ultraviolet LED chip with dual polarization induction doping layer designed by the present invention (see attached Figure 1 and accompanying drawings), characterized in that: from bottom to top, it is composed of a substrate 1, an AlN template layer 2, a composition gradient Al x Ga 1-x N-polarization induced n-type doping layer 3, active region light-emitting layer 4, composition gradient Al y Ga 1-y N polarization induced p-type doped layer 5 composition; in the composition gradient Al y Ga 1- y A p-electrode 6 is arranged on the N-polarization induced p-type doped layer 5, and the active region light emitting layer 4 and the composition gradient Al y Ga 1-y N polarization induces the p-type doped layer 5 to be etched, exposing the Al x Ga 1-x N polarization induces n-type doping layer 3 and the composition gradient Al x Ga 1-x N polarization induces the n-type doping layer 3 to be etched to a certain depth, and then the remaining composition is gradually changed to Al x Ga 1-x An n-electrode 7 is arranged on the N polarization induced n-type doping layer 3; the present invention adopts AlGaN with a gradient composition to realize the high carrier concentration polarization induced n-type and p-type doping of the AlGaN material, which is beneficial to improving the luminescence performance of the AlGaN-based ultraviolet LED; and an AlGaN material matching the composition of the dual polarization induced doping layer is adopted as the active area light-emitting layer, and the chip can be prepared using nitrogen polarity AlGaN material or metal polarity AlGaN material.

[0006] The AlGaN-based ultraviolet LED chip with dual polarization inducing doping layers as described above is characterized in that the substrate 1 can be a sapphire substrate, a SiC substrate, a Si substrate, an AlN substrate or other single crystal substrates that can be used for nitride epitaxial growth.

[0007] The polarity of each layer of material on the substrate 1 can be regulated by the type of substrate or the substrate surface pretreatment process. For example, a nitrogen-polarity AlGaN-based ultraviolet LED can be obtained on a carbon-surface SiC substrate, and a metal-polarity AlGaN-based ultraviolet LED can be obtained on a silicon-surface SiC substrate; a nitrogen-polarity AlGaN-based ultraviolet LED can be obtained on a sapphire and Si substrate that has been subjected to high-temperature nitridation treatment (temperature ≥900°C, treatment time between 10s and 10min), and a metal-polarity AlGaN-based ultraviolet LED can be obtained on a sapphire and Si substrate that has been subjected to low-temperature nitridation treatment (temperature ≤700°C, treatment time between 10s and 10min); a metal-polarity AlGaN-based ultraviolet LED can be obtained on a metal-polarity AlN substrate, and a nitrogen-polarity AlGaN-based ultraviolet LED can be obtained on a nitrogen-polarity AlN substrate.

[0008] The AlGaN-based ultraviolet LED chip with dual polarization induction doping layer is characterized in that: the composition of the AlGaN-based ultraviolet LED chip is gradually changed. x Ga 1-x The Al composition of the N-polarized n-type doped layer 3 changes gradually from x1 to x2 along the epitaxial growth direction, 0≤x1≤1, 0≤x2≤1, and the thickness is 10-200nm; the Al composition changes gradually from x1 to x2 along the epitaxial growth direction, 0≤x1≤1, 0≤x2≤1, and the thickness is 10-200nm; y Ga 1-y The Al composition of the N-polarization induced p-type doped layer 5 changes gradually from y1 to y2 along the epitaxial growth direction, 0≤y1≤1, 0≤y2≤1, and the thickness thereof is 10-200 nm.

[0009] The AlGaN-based ultraviolet LED chip with dual polarization induction doping layer is characterized in that: the active region light emitting layer 4 is Al z1 Ga 1-z1 N single layer or multiple pairs of Al z2 Ga 1-z2 N / A z3 Ga 1-z3 N quantum wells, of which Al z1 Ga 1-z1 The thickness of the N single layer is 1 to 10 nm, 0<z1<1; Al z2 Ga 1-z2 N / A z3 Ga 1-z3 The number of pairs of N quantum wells is 1 to 20, 0<z2<z3<1, Al z3 Ga 1-z3 N thickness is 1~10nm, Al z2 Ga 1-z2 The thickness of N is 5 to 15 nm.

[0010] The AlGaN-based ultraviolet LED chip with a dual polarization induced doping layer as described above is characterized in that: the chip can be a nitrogen-polarity AlGaN-based ultraviolet LED, that is, on a carbon-surface SiC substrate, a sapphire and Si substrate that has been subjected to high-temperature nitridation (temperature ≥ 900°C, treatment time between 10s and 10min) and a nitrogen-polarity AlN substrate 1, an AlN template layer 2, a composition gradient Al x Ga 1-x N-polarization induced n-type doping layer 3, active region light-emitting layer 4, composition gradient Al y Ga 1-y N polarization induced p-type doped layer 5 is along Directional growth; for nitrogen-polar AlGaN-based UV LEDs, the composition gradient Al x Ga 1-x N polarization induced n-type doping layer 3 requires a gradient composition x1>x2, and a gradient Al y Ga 1-y The N-polarization induced p-type doping layer 5 requires a gradient composition y1 < y2, and for the active region light emitting layer Al z1 Ga 1-z1 N single layer requires Al composition z1≤x2 and z1≤y1. For the active area light-emitting layer, multiple pairs of Al z2 Ga 1-z2 N / A z3 Ga 1-z3 N quantum well requires Al composition z2<z3≤x2 and z2<z3≤y1.

[0011] The AlGaN-based ultraviolet LED chip with a dual polarization induced doping layer as described above is characterized in that: the chip can be a metal polarity AlGaN-based ultraviolet LED, that is, on a silicon surface SiC substrate, on a sapphire and Si substrate that has been subjected to low temperature nitridation treatment (temperature ≤ 700°C, treatment time between 10s and 10min) and a metal polarity AlN substrate 1, an AlN template layer 2, a composition gradient Al x Ga 1-x N-polarization induced n-type doping layer 3, active region light-emitting layer 4, composition gradient Al y Ga 1-y N polarization induced p-type doping layer 5 grows along the

[0001] direction; for metal polarity AlGaN-based UV LED, the composition gradient Al x Ga 1-x N polarization induced n-type doping layer 3 requires a gradient composition x1<x2, and a gradient Al y Ga 1-y N polarization induced p-type doping layer 5 requires a gradient composition y1>y2, and for the active region light emitting layer Al z1 Ga 1-z1N single layer requires Al composition z1≤x2 and z1≤y1. For the active area light-emitting layer, multiple pairs of Al z2 Ga 1-z2 N / A z3 Ga 1-z3 N quantum well requires Al composition z2<z3≤x2 and z2<z3≤y1.

[0012] The AlGaN-based ultraviolet LED chip with dual polarization inducing doping layers as described above is characterized in that the thickness of the AlN template layer 2 is 100 nm to 5 μm.

[0013] A method for preparing an AlGaN-based ultraviolet LED chip with a dual polarization inducing doping layer as described above, the steps are as follows:

[0014] (1) Using metal organic chemical vapor deposition (MOCVD) method, AlN template layer 2, composition gradient Al x Ga 1-x N-polarization induced n-type doping layer 3, active region light-emitting layer 4, composition gradient Al y Ga 1-y N polarization induced p-type doped layer 5; wherein the AlN template layer 2 has a growth temperature of 1000-1200°C, a growth pressure of 100-400 mbar, a thickness of 100-5000 nm, and a growth source of trimethylaluminum and high-purity ammonia; the composition is gradually changed to Al x Ga 1-x The growth temperature of the N-polarization induced n-type doped layer 3 is 1000-1200°C, the growth pressure is 100-400 mbar, the thickness is 10-200 nm, the growth source is trimethylaluminum, trimethylgallium and high-purity ammonia, the doping source is silane, and the doping concentration is 10 17 ~10 21 / cm 3 , its component gradient can be achieved by gradually changing the source flow rate during the growth process, for example, the Al component gradient can be achieved by linearly increasing the trimethylaluminum flow rate during the growth process, while linearly reducing the trimethylgallium flow rate (or the trimethylaluminum flow rate remains unchanged, while the trimethylgallium flow rate is linearly reduced, corresponding to the embodiment); conversely, the Al component gradient can be achieved by linearly reducing the trimethylaluminum flow rate during the growth process, while linearly increasing the trimethylgallium flow rate (or the trimethylaluminum flow rate remains unchanged, while the trimethylgallium flow rate is linearly increased, corresponding to the embodiment); the growth temperature of the active region light-emitting layer 4 is 1000-1200°C, the growth pressure is 100-400mbar, the thickness is 5-15nm, and the growth sources are trimethylaluminum, trimethylgallium and high-purity ammonia; the component gradient Al y Ga 1-yThe growth temperature of the N-polarization induced p-type doped layer 5 is 1000-1200°C, the growth pressure is 100-400 mbar, the thickness is 10-200 nm, the growth source is trimethylaluminum, trimethylgallium and high-purity ammonia, the doping source is bis(cyclopentadienyl)magnesium, and the doping concentration is 10 17 ~10 21 / cm 3 , the gradual change of the components can be achieved by gradually changing the source flow rate during the growth process, for example, the gradual increase of the Al component can be achieved by linearly increasing the trimethylaluminum flow rate during the growth process, while linearly reducing the trimethylgallium flow rate (or the trimethylaluminum flow rate remains unchanged, while the trimethylgallium flow rate is linearly reduced, corresponding to the embodiment); conversely, the gradual decrease of the Al component can be achieved by linearly reducing the trimethylaluminum flow rate during the growth process, while linearly increasing the trimethylgallium flow rate (or the trimethylaluminum flow rate remains unchanged, while the trimethylgallium flow rate is linearly increased, corresponding to the embodiment);

[0015] (2) Composition gradient Al y Ga 1-y The area on one side of the upper surface of the N-polarization induced p-type doped layer 5 is etched by ICP method to the composition gradient Al x Ga 1-x N polarization induces n-type doping layer 3, resulting in exposed Al x Ga 1-x N polarization induces n-type doped layer 3 mesa; in the composition gradient Al y Ga 1-y A p-electrode 6 (thickness 30-120 nm) is prepared on the N-polarization induced p-type doped layer 5, and a gradient Al x Ga 1-x An n-electrode 7 (thickness 60-300 nm) is prepared on the surface of the N-polarization induced n-type doped layer 3; the material of the p-electrode can be a single-layer material such as Au, Pt, a binary alloy composite material such as Ni-Au, Ni-Pt, or a ternary composite material such as Ni-Pt-Au; the material of the n-electrode can be a binary alloy composite material such as Ti-Au, a ternary alloy composite material such as Ti-Al-Au, or a quaternary alloy composite material such as Ti-Al-Ni-Au, Ti-Al-Ti-Au; the substrate 1 is polished and thinned, and then split to obtain an AlGaN-based ultraviolet LED chip.

[0016] Effects and benefits of the present invention: ① The high carrier concentration polarization induced n-type and p-type doping of AlGaN material is achieved by using AlGaN with a gradient composition, which is beneficial to improving the luminescence performance of AlGaN-based ultraviolet LEDs; ② The AlGaN with a gradient composition x Ga 1-x N polarization induced n-type doping layer can effectively alleviate the lattice mismatch between the active region and the template layer and reduce the mismatch dislocation density; ③ Gradient Al yGa 1-y N polarization induces p-type doping layer to provide holes, while effectively blocking electrons from overflowing from the active area. There is no need to grow an additional fixed-composition AlGaN electron blocking layer, which can simplify the LED manufacturing process; ④ Using a gradient Al y Ga 1-y The N-polarization induced p-type doping layer can eliminate the absorption of ultraviolet light in the active region by the p-GaN layer in the traditional ultraviolet LED structure. Therefore, the method of the present invention can realize the high-efficiency light emission of AlGaN-based ultraviolet LED. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 : Schematic diagram of the structure of the AlGaN-based ultraviolet LED with dual polarization induced doping layer described in the present invention.

[0018] Figure 2 : Schematic diagram of the energy band structure of the AlGaN-based ultraviolet LED with dual polarization-induced doping layer prepared in Example 1, with a gradient Al y Ga 1-y The N-polarization induced p-type doping layer 5 can be used as an electron blocking layer to effectively block the electron overflow, while it has no blocking effect on hole injection; and the composition gradient Al x Ga 1-x The N-polarization induced n-type doping layer 3 can be used as a hole blocking layer to effectively block the overflow of holes, while it has no blocking effect on electron injection.

[0019] Figure 3 : Comparison of the emission spectra of the AlGaN-based ultraviolet LED with dual polarization inducing doping layer prepared in Example 1 and the AlGaN-based ultraviolet LED with traditional fixed component doping layer under a driving current of 20mA.

[0020] In the figure, 1 is the substrate, 2 is the AlN template layer, and 3 is the composition gradient Al x Ga 1-x N polarization induced n-type doping layer, 4 is the active area light-emitting layer, 5 is the composition gradient Al y Ga 1-y N polarization induces p-type doped layer, 6 is the p-electrode, and 7 is the n-electrode. DETAILED DESCRIPTION

[0021] The specific embodiments of the present invention are described in detail below in combination with the technical solutions and the accompanying drawings.

[0022] Embodiment 1:

[0023] 1. Using the MOCVD method, an AlGaN-based UV LED structure with a dual polarization-induced doping layer was epitaxially prepared on a commercial carbon-surface SiC substrate with a 4° bevel angle, such as Figure 1The specific structure is as follows: a nitrogen-polar AlN template layer 2 (thickness 500nm), a composition gradient Al x Ga 1-x N polarization induced n-type doping layer 3 (Al composition linearly changes from x1 = 0.8 to x2 = 0.6, thickness is 100nm, doping concentration is 5×10 18 / cm 3 During the growth process, the flow rates of ammonia and trimethylaluminum were kept constant, and the flow rate of trimethylgallium source increased linearly from 15.7 μmol / min to 29.9 μmol / min. The growth time was 900 s, and the active region light emitting layer 4 (Al 0.5 Ga 0.5 The thickness of the N layer is 4nm, and the layer is undoped), the composition is gradually changed to Al y Ga 1- y N polarization induced p-type doping layer 5 (Al composition linearly changes from y1 = 0.6 to y2 = 0.8, thickness is 100nm, doping concentration is 2×10 19 / cm 3 During the growth process, the flow rates of ammonia and trimethylaluminum were kept constant, and the flow rate of trimethylgallium source was linearly reduced from 29.9μmol / min to 15.7μmol / min, and the growth time was 900s. The growth sources were trimethylaluminum, trimethylgallium and high-purity ammonia, with H2 as the carrier gas, and silane and bismuth magnesium were used for n-type and p-type doping respectively. Except for the growth temperature of nitrogen-polar AlN template layer 2 at 1120℃, the growth temperature of the remaining layers was 1100℃, and the growth pressure of each layer was 100mbar. The specific growth parameters of each layer of the device are shown in Table 1.

[0024] Table 1: Growth parameters of each layer of the AlGaN-based UV LED with dual polarization-induced doping layer in Example 1

[0025]

[0026]

[0027] Note: TMGa stands for trimethylgallium; TMAl stands for trimethylaluminum; Cp2Mg stands for bismuthocene magnesium; SiH4 stands for silane; NH3 stands for high-purity ammonia.

[0028] 2. In the composition gradient Al y Ga 1-y The area on one side of the upper surface of the N-polarization induced p-type doped layer 5 is etched by ICP etching method (using boron chloride and chlorine gas with a gas flow ratio of 1:9 and a plate power of 100W) to the composition gradient Al x Ga 1-xN polarization induces n-type doping layer 3, resulting in exposed Al x Ga 1-x N polarization induces n-type doping layer 3 mesa; thermal evaporation method is used to expose the composition gradient Al x Ga 1-x The n-electrode 7 made of Ti / Al / Ti / Au (thickness of 260nm, thickness of each layer of 40nm, 150nm, 20nm, 50nm, evaporation sources of Ti metal, Al metal and Au metal, evaporation rates of 3.6nm / min, 4.8nm / min, 2.4nm / min, respectively) was prepared on the surface of the N-polarization induced n-type doped layer 3, and then the composition gradient Al was not etched by thermal evaporation. y Ga 1-y On the N polarization induced p-type doping layer 5, a p-electrode 6 made of Ni-Au binary alloy (thickness 60nm, Ni layer thickness 30nm, Au layer thickness 30nm, evaporation sources Ni metal and Au metal, evaporation rates 3.6nm / min and 2.4nm / min, respectively) is prepared, thereby obtaining an AlGaN-based ultraviolet LED chip with a dual polarization induced doping layer. The specific preparation process of the electrode is shown in Table 2. Finally, the substrate 1 is polished and thinned, and then split to obtain an AlGaN-based ultraviolet LED chip.

[0029] Table 2: Device electrode preparation process parameters

[0030]

[0031]

[0032] 3. Figure 2 The energy band structure diagram of the AlGaN-based ultraviolet LED with dual polarization induction doping layer prepared in Example 1. From the energy band diagram, it can be seen that the composition of the AlGaN-based ultraviolet LED is gradually changed. y Ga 1-y The N-polarization induced p-type doped layer can act as an electron blocking layer, effectively blocking electron overflow, while it has no blocking effect on hole injection; and the composition gradient Al x Ga 1-x The N-polarization induced n-type doped layer can be used as a hole blocking layer to effectively block hole overflow, while it has no blocking effect on electron injection.

[0033] 4. Figure 3The figure shows the electroluminescence spectrum comparison of the dual polarization induction doped layer AlGaN-based ultraviolet LED prepared in Example 1 and the conventional fixed component doped layer AlGaN-based ultraviolet LED under a driving current of 20 mA. In the conventional fixed component doped layer AlGaN-based ultraviolet LED structure, except for the n-type AlGaN electron supply layer and the p-type AlGaN hole supply layer using a fixed component n-type AlGaN, the p-type AlGaN hole supply layer is a fixed component n-type AlGaN. 0.7 Ga 0.3 N and p-type Al 0.7 Ga 0.3 Except for N, the rest of the structure and the doping concentration and thickness of the doping layer are consistent with those of the AlGaN-based UV LED with dual polarization induced doping layer. Figure 3 It can be seen that the emission wavelengths of the two ultraviolet LEDs are both around 280nm, but the emission intensity of the AlGaN-based ultraviolet LED with a dual polarization induced doping layer prepared by the present invention is much higher than that of the AlGaN-based ultraviolet LED with a traditional fixed component doping layer. The superiority of the scheme of the present invention can be seen from the results.

Claims

1. An AlGaN-based ultraviolet LED chip with dual polarization induction doping layer, which comprises, from bottom to top, a substrate (1), an AlN template layer (2), a composition gradient Al x Ga 1-x N-polarization induced n-type doping layer (3), active region light-emitting layer (4), composition gradient Al y Ga 1-y N polarization induced p-type doped layer (5) composition; in the composition gradient Al y Ga 1-y A p-electrode (6) is arranged on the N-polarization induced p-type doping layer (5), and the active region light emitting layer (4) and the component gradient Al y Ga 1-y N polarization induces the p-type doped layer (5) to be etched to expose the composition gradient Al x Ga 1-x N polarization induces n-type doping layer (3) and the composition gradient Al x Ga 1-x The N-type doped layer (3) is etched to a certain depth by N polarization induction, and then the remaining composition is gradually changed to Al x Ga 1-x An n-electrode (7) is arranged on the N-polarization induced n-type doping layer (3); the substrate (1) is a sapphire substrate, a SiC substrate, a Si substrate or an AlN substrate; the characteristics are: The chip is a nitrogen-polar AlGaN-based ultraviolet LED, the substrate (1) is a carbon-surface SiC substrate, a sapphire or Si substrate that has been subjected to high-temperature nitridation, or a nitrogen-polar AlN substrate, the AlN template layer (2), a composition gradient Al x Ga 1-x N-polarization induced n-type doping layer (3), active region light-emitting layer (4), composition gradient Al y Ga 1-y The N-polarization induced p-type doped layer (5) is along [000 ] direction growth; composition gradient Al x Ga 1-x The N polarization induced n-type doped layer (3) has an Al composition gradually changing from x1 to x2 along the epitaxial growth direction, 0≤x1≤1, 0≤x2≤1, and x1>x2, and a thickness of 10~200 nm; the Al composition gradually changing from x1 to x2 y Ga 1-y The N polarization induced p-type doped layer (5) has an Al composition gradually changing from y1 to y2 along the epitaxial growth direction, 0≤y1≤1, 0≤y2≤1, and y1<y2, and a thickness of 10~200 nm; the active region light emitting layer (4) is Al z1 Ga 1-z1 N single layer or multiple pairs of Al z2 Ga 1-z2 N / A z3 Ga 1-z3 N quantum wells, of which Al z1 Ga 1-z1 The thickness of the N single layer is 1~10 nm, 0<z1<1, z1≤x2, z1≤y1; Al z2 Ga 1-z2 N / A z3 Ga 1-z3 The number of pairs of N quantum wells is 1~20, 0<z2<z3<1, where z2<z3≤x2 and z2<z3≤y1, Al z3 Ga 1-z3 N thickness is 1~10 nm, Al z2 Ga 1-z2 N thickness is 5~15 nm.

2. The AlGaN-based ultraviolet LED chip with dual polarization inducing doping layer as claimed in claim 1, characterized in that: The thickness of the AlN template layer (2) is 100 nm to 5 μm, the thickness of the p-electrode (6) is 30 to 120 nm, and the thickness of the n-electrode (7) is 60 to 300 nm.

3. The AlGaN-based ultraviolet LED chip with dual polarization inducing doping layer as claimed in claim 1, characterized in that: The material of the p-electrode (6) is a unitary, binary or ternary alloy material such as Au, Pt, Ni-Au, Ni-Pt or Ni-Pt-Au, and the material of the n-electrode (7) is a binary, ternary or quaternary alloy material such as Ti-Au, Ti-Al-Au, Ti-Al-Ni-Au or Ti-Al-Ti-Au.

4. The method for preparing an AlGaN-based ultraviolet LED chip with a dual polarization inducing doping layer according to claim 1, wherein the steps are as follows: 1) Using a metal organic compound chemical vapor deposition method, an AlN template layer (2), a composition gradient Al x Ga 1-x N-polarization induced n-type doping layer (3), active region light-emitting layer (4), composition gradient Al y Ga 1-y N polarization induced p-type doping layer (5); wherein the growth temperature of the AlN template layer (2) is 1000~1200 o C, growth pressure is 100~400 mbar, growth source is trimethylaluminum and high-purity ammonia; composition gradient Al x Ga 1-x The growth temperature of the N-polarization induced n-type doped layer (3) is 1000~1200 o C, the growth pressure is 100~400 mbar, the growth sources are trimethylaluminum, trimethylgallium and high-purity ammonia, the doping source is silane, and the doping concentration is 10 17 ~10 21 / cm 3 The growth temperature of the active region light emitting layer (4) is 1000~1200 o C, the growth pressure is 100~400 mbar, the growth source is trimethylaluminum, trimethylgallium and high-purity ammonia; the composition is gradually changed to Al y Ga 1-y The growth temperature of the N-polarization induced p-type doped layer (5) is 1000~1200 o C, the growth pressure is 100~400 mbar, the growth sources are trimethylaluminum, trimethylgallium and high-purity ammonia, the doping source is bis(cyclopentadienyl)magnesium, and the doping concentration is 10 17 ~10 21 / cm 3 ; 2) Composition gradient Al y Ga 1-y The area on one side of the upper surface of the N-polarization induced p-type doped layer (5) is etched by ICP method to a composition gradient Al x Ga 1-x N polarization induces n-type doping layer (3), resulting in exposed compositionally graded Al x Ga 1-x N polarization induces n-type doped layer (3) table; in the composition gradient Al y Ga 1-y A p-electrode (6) is prepared on the N-polarization induced p-type doping layer (5) by a thermal evaporation method, and a gradient Al x Ga 1-x An n-electrode (7) is prepared on the surface of the N-polarization induced n-type doping layer (3) by a thermal evaporation method, thereby preparing an AlGaN-based ultraviolet LED device with a dual-polarization induced doping layer; the substrate (1) is further polished and thinned, and then split to obtain an AlGaN-based ultraviolet LED chip.

Citation Information

Patent Citations

  • Dopant-free AlGaN-based ultraviolet light-emitting diode and preparation method

    CN104882522A

  • Nitrogen-containing polar blue-violet LED chip with polarization-induced p-type doping layer and preparation method

    CN107978661A

  • AlGaN-based tunneling junction structure based on polarization induced principle and preparation method thereof

    CN109786531A

  • MoS2-based thin-layer ultraviolet light-emitting diode and manufacturing method thereof

    CN111146318A